Retained strength of UHTCMCs after oxidation at 2278 K. (October 2021) - Galizia, Pietro; Vinci, Antonio; Zoli, Luca; Monteverde, Frederic; Binner, Jon; Venkatachalam, Vinothini; Lagos, Miguel.A.; Reimer, Thomas; Jain, Neraj; Sciti, Diletta
Highlights: Studied the strength retention of 4 classes of UHTCMCs after oxidation at 2000 °C in air. Short fibre based UHTCMCs showed the highest strength retention, >80% For long fibre reinforced UHTCMCs, strength retention was proportional to the UHTC content. All ZrB2 -based UHTCMCs withstood severe temperatures with a good degree of strength retention. Abstract: In the frame of Horizon 2020 European C 3 HARME research project, the manufacture of ZrB2 -based CMCs was developed through different processes: slurry infiltration and sintering, radio frequency chemical vapour infiltration (RF-CVI) and reactive metal infiltration (RMI). To assess the high temperature stability, room temperature bending strength was measured after oxidizing the samples at 2278 K and compared to the strength of the as-produced materials. Microstructures were analysed before and after the thermal treatment to assess the damage induced by the high temperature oxidation. Short fibre-reinforced composites showed the highest retained strength (>80%) and an unchanged stress–strain curve.